A galenical produced from Ba‐Wei‐Die‐Huang‐Wan (THC‐002) provides resistance to the cold stress‐induced detrusor overactivity in conscious rats12. Issue 5 (31st December 2012) - Imamura, Tetsuya; Ishizuka, Osamu; Sudha, Gautam Silwal; Lei, Zhang; Hosoda, Tomoka; Noguchi, Wataru; Yamagishi, Takahiro; Yokoyama, Hitoshi; Kurizaki, Yoshiki; Nishizawa, Osamu
Abstract Aims We determined if THC‐002, a galenical produced from Ba‐Wei‐Die‐Huang‐Wan, could increase skin temperature and inhibit detrusor overactivity induced by sudden whole body cooling. Further, we determined if THC‐002 could decrease expression of transient receptor potential melastatin 8 (TRPM8) channels associated with the cold responses. Methods Hind leg skin temperature of female 10‐week‐old Sprague–Dawley rats was measured by thermal imaging. Experimental rats (n = 12) were given oral 100 mg/kg THC‐002 daily for one week, and controls (n = 12) were similarly treated with THC‐002‐free solution. Afterwards, thermal imaging and cystometric investigations of the freely moving conscious rats were performed at room temperature (RT, 27 ± 2°C) for 20 min. The rats were then transferred to a low temperature (LT, 4 ± 2°C) environment during which thermal imaging and cystometric measurements were taken at 5, 10, 20, 30, and 40 min. Afterward, the skin tissues were harvested to estimate expression levels of TRPM8 channels by immunohistochemistry and real‐time reverse‐transcription polymerase chain reaction. Results The RT skin temperature of THC‐002‐treated rats was significantly higher than controls. During the first 20 min under LT, the control rats exhibited cold stress‐induced detrusor overactivity such as decreased voiding interval and bladder capacity. THC‐002 partially inhibited the detrusor overactivity patterns. During the second 20 min, skin temperature was relatively stable, and the detrusor overactivity of both groups slowly disappeared. THC‐002 significantly reduced expression of TRPM8 channel protein and mRNA. Conclusions THC‐002 inhibited cold stress‐induced detrusor overactivity resulting from decreasing skin temperature. Therefore, THC‐002 might provide resistance to cold stress‐exacerbated lower urinary tract symptoms. Neurourol. Urodynam. 32: 486–492, 2013. © 2012 Wiley Periodicals, Inc.